Remystifying Scriabin: Scalar Quality in the Late Works - Lal, Rajan (Apollo - University of Cambridge Repository, 2024)
This thesis offers close analyses of several late compositions (1907-1915) by Alexander Scriabin. All the pieces considered have, for one reason or another, proven difficult for scholarship to grasp from a technical perspective. Published works considered range from the Fifth Piano Sonata, Op. 53 to the Five Preludes, Op. 74. Sections from the extant Prefatory Action sketches are also analysed. Several established analytical tools are employed: Schenkerian analysis, Pitch-Class Set Theory, Scalar Theory, sonata-focused theories of form, and notions of ‘Russian’ modular discontinuity. Often, the employment of one method occurs in tandem with another, or others, to generate revealing counterpoises. A novel analytical tool that I call ‘Scalar Quality’ is also theorised, bringing set-theoretical and scalar transformational considerations into contact with sonic characteristics abstracted from diatonic tonality (seventh types and unstable ‘rare-interval’ tritones). Thus, one potential tension/relaxation dynamic possible between non-diatonic collections is uncovered, sensitive to both intervallic content and spacing/voicing parameters. With ‘Scalar Quality’ in play, this thesis seeks better to understand Scriabin’s most enigmatic works with the tools that seem most appropriate. Ultimately, there is a unifying strand. Five case studies and several small analytical vignettes demonstrate that an architectonic view of this music is favourable. Scriabin’s sonorities are decidedly post-tonal (post-diatonic, post-functional) when isolated as raw resources, though his handling of them within musical structure betrays considerable hallmarks of a tonal inheritance and, sometimes, its simultaneous misreading. The thesis is tripartite in design and bottom-heavy: Part I, composed of Chapter I, introduces the problems that confront the analyst of Scriabin’s late music. A close reading of the slow introduction to the Eighth Piano Sonata, Op. 66 follows, serving as an ‘analytical appetiser’. Though existing interfaces can shed much light on the abstruse harmonic language of this section, I argue that there is a need to introduce a new tool, in tandem with present apparatuses, fully to understand this passage. Part II consists of Chapter II and Chapter III. Chapter II provides an outline of existing analytical approaches to Scriabin’s late music. A salient spectral distribution to the scholarship Page 3 of 360 is identified, followed by a majority two-part grouping. Scriabin’s works are analysed either through the lens of extension of the tonal tradition or through the lens of set-class organisation. One viewpoint derives from that which came before; another anticipates, by implication, the music to come. I argue that this bifurcation is as unhelpful as the age-old question of ‘tonal oder atonal?’, and that we need to approach this repertoire through exploration of the tension/relaxation dynamics enacted by Scriabin’s repository of non-diatonic ‘sets’. In short, we need to understand post-tonal pitch resources ‘tonally’. In Chapter III, a novel notion of ‘Scalar Quality’ is thus proposed, drawing on the writings of Anthony Pople, Vasilis Kallis, Jim Samson, and Kenneth Smith. ‘Scalar Quality’ permits the ranking of Scriabin’s sonorities along a fluid spectrum ranging from concrete sonic stability (I-Quality status) to high sonic instability (V-Quality status). Part III, comprising Chapters IV, V, VI, VII and VIII, provides several analytical case studies that seek better to understand problem pieces from Scriabin’s output. Chapter IV considers the Fifth Sonata, Op. 53, through the lens of scalar diatonicism, the Quality status of structural modules, and structural voice-leading. Chapter V examines one theme from the Tenth Sonata, Op. 70, before placing this structural unit within the wider rotational strategy of the work. Chapter VI considers the Prelude, Op. 74/v in the context of its set of five, focussing on the role non-diatonic collections play at various structural levels. Chapter VII returns to the Eighth Sonata in full to consider the notion of a Two-Dimensional, post-tonal sonata form in mature realisation. Chapter VIII examines hitherto unexplored passages from the Prefatory Action sketches. A two-part conclusion follows. There, the strands of all previous analyses are drawn together to present a nuanced architectonic view of Scriabin’s late music, one that moves beyond ‘tonal oder atonal?’ questions endemic to the composer’s literature and that of his contemporaries. Further thoughts are offered on ‘Scalar Quality’ as a generalised system of tension and release for both music at the precipice of tonality and music of a definitively post-tonal nature. The thesis closes with a ‘palate cleanser’ analysis of Schoenberg’s Op. 19/ii.
Keywords: Scriabin; music analysis; Schoenberg